Management of Proclined Anterior Teeth by Digital Smile Designing – A Case Report - Dudhe, Surabhi Pravin; Gadbail, Amol; Madhavi, Ashima; Bajaj, Rajat; Bajaj, Namarata (Journal of Neonatal Surgery, 2025)
A smile is a person’s greatest beauty. A smile is an important facial expression – expressing friendliness, agreement and appreciation. Smile requires co-ordination of facial, gingival and dental components stimulated voluntarily or involuntarily by various emotions –Crawford. Smile design is the planning and pre-visualization of the desired end result of an esthetical dental treatment, targeting a more harmonious state instead of the current disharmony. It is interesting to note that smile has a role to play in the overall health and well- being of a person. According to Jane Lyle, author of the book “Body Language”, many experts are convinced that smiling and laughing is beneficial to one’s health. Psychologist Robert Zajconc has postulated that when a person smiles deliberately the brain releases neurotransmitters which can override the sadness. Paul Ekman, a researcher at the University of California supports this theory. When people’s faces are happy, heart rates slowed and the bodies become calm. Mr Christian Coachman, a Brazilian dentist/ dental tech, first introduced the concept of DSD, a dental treatment planning tool used for enhancing predictability, improving communication, and strengthening vision .The purpose of this case report was to present an integrated design approach that took into account functional, esthetic , and emotional aspects of the patient's needs.